Advances in Conceptual and Methodological Issues in Symptom Cluster Research: A 20-Year Perspective. (28th October 2022) - Harris, Carolyn S.; Dodd, Marylin; Kober, Kord M.; Dhruva, Anand A.; Hammer, Marilyn J.; Conley, Yvette P.; Miaskowski, Christine A.
Abstract : Two conceptual approaches are used to evaluate symptom clusters: "clustering" symptoms (ie, variable-centered analytic approach) and "clustering" patients (ie, person-centered analytic approach). However, these methods are not used consistently and conceptual clarity is needed. Given the emergence of novel methods to evaluate symptom clusters, a review of the conceptual basis for older and newer analytic methods is warranted. Therefore, this article will review the conceptual basis for symptom cluster research; compare and contrast the conceptual basis for using variable-centered versus patient-centered analytic approaches in symptom cluster research; review their strengths and weaknesses; and compare their applications in symptom cluster research.